Ramp-rate control approach based on dynamic smoothing parameter to mitigate solar PV output fluctuations - Sukumar S.; Mokhlis H.; Mekhilef S.; Karimi M.; Raza S. (Elsevier Ltd, 2023)
Electric power supplies to apparatus; Energy resources; Battery energy storages (BES); Exponential smoothing; Moving averages; Output fluctuations; PV smoothing; Ramp rates; Smoothing parameter; Solar PVs; Energy storage